Submillisecond fireball timing using de Bruijn timecodes - Howie, R.; Paxman, J.; Bland, Phil; Towner, Martin; Sansom, E.; Devillepoix, H. (John Wiley & Sons, Inc., 2017)
Long-exposure fireball photographs have been used to systematically record meteoroid trajectories, calculate heliocentric orbits, and determine meteorite fall positions since the mid-20th century. Periodic shuttering is used to determine meteoroid velocity, but up until this point, a separate method of precisely determining the arrival time of a meteoroid was required. We show it is possible to encode precise arrival times directly into the meteor image by driving the periodic shutter according to a particular pattern-a de Bruijn sequence-and eliminate the need for a separate subsystem to record absolute fireball timing. The Desert Fireball Network has implemented this approach using a microcontroller driven electro-optic shutter synchronized with GNSS UTC time to create small, simple, and cost-effective high-precision fireball observatories with submillisecond timing accuracy.